Evaluating ski friction as a function of velocity using optical flow and Hall effect sensors - Kirby, R.; Karlöf, L. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
The purposes of our paper are to 1) present a new measurement system for testing ski glide characteristics that produces high sample rate velocity vs. time measurements using image alignment techniques and Hall effect sensors, 2) validate the system in the laboratory, and 3) evaluate the system in real-world glide testing with professional glide testers.